THE DYNAMICS OF INDICATORS OF PSYCHO-EMOTIONAL CONDITION OF COLLEGE STUDENTS, INFLUENCED BY TEAMBUILDING TECHNOLOGIES - Semenova, Nataliia; Rymar, Olga; Khanikiants, Olena; Malanchuk, Halyna; Lapychak, Ihor (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Specialists say that the issue of understanding of influence mechanism of physical activity on psychological health of children and teenagers is not investigated thoroughly. This concerns primarilycollege students, fortheir age equals to that of high school pupils.Psycho-emotional processes in the students’ consciousness and behavior atthat ageare caused by the end of biological and physical development and adaptation to new conditions of studying and living. Our previous research allowed us to determine the condition and dynamics of psycho-emotional indicators during the first academic year against the background of low physical activity. The question of how particular physical activity influences the dynamics of these indicators among college students remains to be unanswered. The aim of the research is to determine the dynamics of indicators of psycho-emotional condition among 15–16 years old students from Medical College. Research methods and techniques like analysis and generalization of scientific literature, documentation, pedagogical observation, SAN and mathematical statistics were applied. The results of the research. Any reliable changes towards either more positive or negative side have not been detected among students from Experimental Group (EG), though indicators of well-being and mood of students from Control Group (CG) have considerably decreased (p≤0,05) during the pedagogical experiment. The reliable deterioration of the CG students’ well-beingfrom have been noticed in comparison with the EG students on the 2nd stage of the experiment. The conclusions. The data obtained from the pedagogical experiment have proved the positive effect of implementation of team-building techniques into physical education of college students on their psycho-emotional condition indicators.